Occurrence of Actinobacillus actinomycetemcomitans in patients with chronic periodontitis, aggressive periodontitis, healthy subjects and children with gingivitis in two cities of the state of São Paulo, Brazil Ocorrência de Actinobacillus actinomycetemcomitans em pacientes com periodontite crônica, periodontite agressiva, pessoas saudáveis e crianças com gengivite em duas cidades do Estado de São Paulo, Brasil - Elerson Gaetti Jardim Júnior; Joseane Maria Dias Bosco; Angélica Marquezim Lopes; Luís Fernando Landucci; Ellen Cristina Gaetti Jardim; Sílvia Rosana Soares Carneiro (University of São Paulo, 2006)
The aim of this study was to determine the frequency of isolation of Actinobacillus actinomycetemcomitans (Aa) in 100 patients with chronic periodontitis, 14 patients with aggressive periodontitis, 142 pre-school children with gingivitis and 134 periodontally healthy subjects. Samples of subgingival plaque were taken using sterilized paper points introduced into periodontal pockets or gingival crevice for 60 seconds and inoculated on TSBV agar, which was incubated under anaerobiosis at 37ºC, for 4 days. Microbial identification was performed through biochemical methods and morphocellular and morphocolonial analysis. Aa was detected in 40.3% of healthy subjects, 68% of patients with chronic periodontitis, 92.86% of patients with aggressive periodontitis and 40.14% of children with gingivitis. The rate of recovery of Aa in the tested human groups proved to be higher than previously reported and in agreement with participation of this facultative anaerobe as a member of native microbiota of the periodontium and its relation with aggressive and chronic periodontitis in Brazil. Avaliou-se a ocorrência de Actinobacillus actinmycetemcomitans (Aa) em pacientes 100 pacientes com periodontite crônica, 14 com doença periodontal agressiva, 142 crianças com gengivite em idade pré-escolar e 134 indivíduos adultos saudáveis. Amostras de placa subgengival foram coletadas usando cones de papel estéreis introduzidos nas bolsas periodontais ou no sulco gengival por 60 segundos e inoculadas em ágar TSBV, que foram incubadas em anaerobiose a 37ºC, por 4 dias. A identificação microbiana foi realizada através de análises bioquímicas, morfocelulares e morfocoloniais. Aa foi detectado em 40,3% de indivíduos saudáveis, 68% de pacientes com periodontite crônica, 92,86% de pacientes com periodontite agressiva e 40,14% das crianças com gengivite. A taxa de ocorrência de Aa nos grupos testados provou ser mais alta do que a previamente descrita na literatura e que esse microrganismo é membro freqüente da microbiota de indivíduos adultos periodontalmente sadios e de crianças com idade pré-escolar com gengivite além de sua relação com a periodontite crônica e agressiva no Brasil.